Timber, cocoa, and crop-raiding elephants: a preliminary study from southern Ghana - Richard Barnes; Sylvester Azika; B. Asamoah-Boateng (Pachyderm)
Reviews the economics associated land use changes in the area initially related to logging and more recently to cocoa and other agricultural crops, which have caused disruption to elephant populations and increased human-elephant conflict in southern Ghana.